The Influence of Female Sex Worker Fellows Support and Motivation on Sexually Transmitted Diseases (STDs) Prevention Behaviors in Makassar City, Indonesia - Zulhijriani, Zulhijriani; Lestari, Nur Cahyani Ari; Muriana, Eviyati Aini; Marlinawati, Iin Tri; Setyanti, Dian Shofia Reny; Sari, Putri Yunita (GHMJ (Global Health Management Journal), 2024)
Background: A sexually transmitted diseases (STDs) is an illness that is primarily transmitted through sexual contact. There are around 30 different species of microorganisms, including bacteria, viruses, and parasites, that can be transmitted through sexual activity without protection. The most prevalent conditions include gonorrhea, chlamydia, syphilis, trichomoniasis, chancroid, genital herpes, HIV, and hepatitis B. Within society, sexually transmitted diseases (STDs) are the most prevalent form of infection. Aims: The objective of this study is to ascertain the direct and indirect impact on the prevention of sexually transmitted illnesses in the city of Makassar. Methods: This study used a cross-sectional design. The study collected samples from 45 consenting individuals who agreed to participate. This study used a structure equation model as an analysis method using Smart PLS 2.0. Results: The findings demonstrated a significant correlation between the support of fellow female sex workers (FSWs) and the practice of STDs prevention, with a direct impact of 10.26%. Additionally, there was a direct influence of STDs prevention behavior on motivation, accounting for 10.84%. Furthermore, the support of fellow FSWs had a substantial impact on motivation, with a direct influence of 29.16%. The overall direct effects have increased by 50.26%. The support of fellow FSWs has an indirect influence on STDs prevention behavior, increasing motivation by 5.77%. The cumulative impact, both direct and indirect, amounts to 56.03%. The Q-Square analysis model accounts for 44.1% of the variability in the data and specifically investigates the phenomenon studied. The remaining 55.9% of variability is attributed to other variables that were not addressed in this study.  Conclusion: Hence, the research findings indicate that various factors, including the assistance from fellow female sex workers and motivation, contribute to the promotion of STDs prevention behavior.   Received: 14 December 2023, Reviewed: 25 December 2023, Revised: 06 January 2024, Accepted: 16 January 2024.